Uncommon Presentation Of Bowen′s Disease - Dawn Goutam; Das Ashim; Kumar Bhushan (Wolters Kluwer Medknow Publications, 1995)
Bowenâ€s disease is desired as persistent, progressive, non- elevated, red scarry or crusted plaque, which is due to an intraepidermal carcinoma and is potentially malignant. Sunlight is considered as an important aetiological factor. In the past; arsenic exposure was also said to be important 1. The curaneous lesion of Bowenâ€s disease can sometimes be hyperkeratotic or fissured 2. Morphology can vary depending on site of involvement.